Unemployment: Macroeconomic performance and the labour market - Layard, R; Nickell, S; Jackman, R (Oxford University Press, 1991)
Develops a general framework for analyzing unemployment, combining macroeconomics with microeconomic analysis of the labor market. Overviews the influences determining unemployment. Analyzes wage bargaining and unions, efficiency wages, wage behavior, the duration of unemployment, the structure of unemployment, prices and the employment behavior of firms, the macroeconomics of unemployment, postwar unemployment in OECD countries, and policies to reduce unemployment. Layard and Jackman are at the London School of Economics. Nickell is at Oxford University. Name and subject indexes.